Body awareness and dyspraxia: between theory and practice - Magnanini, Angela; Pannone, Chiara (Revista Eletrônica de Educação, 2024)
This essay aims to address a gap in the educational literature, specifically the limited studies on dyspraxia and potential interventions in schools. By intertwining theoretical and practical dimensions, the essay seeks to elucidate how to effectively intervene with children with dyspraxia within an educational setting. The embodied cognition perspective recommends early engagement with body awareness to address the educational needs and enhance the skills of children with dyspraxia. Following a theoretical introduction, the essay provides practical guidance for teachers, divided into six distinct areas. The authors advocate an inclusive approach, emphasising the importance of not only focusing on the child with dyspraxia but also involving the whole class. This inclusive perspective is believed to be beneficial for all pupils.